SCHOOL DISEASES IN COPAINALÁ, CHIAPAS (1880-1926) - Oscar Janiere Martínez Ruiz (IJRDO - Journal of Social Science and Humanities Research, 2026)
The article is conceived as a case study, of a historiographical nature, which historically reconstructs the main school diseases present in Copainalá, Chiapas, during the transition from the 19th to the 20th century. It examines the presence of recurring infectious diseases in a region characterized by its population of Zoque origin, as well as the ongoing occurrence of viral epidemics, in order to show how they affected health in primary schools. The number of child deaths recorded in the Civil Registry serves as the main source of information for the period from 1917 to 1926, which is compared with the sanitary conditions in the region and the educational policies of the time, in order to understand the impact of school diseases and the role played by schools within the educational sphere. The central argument of the article holds that the school, despite being a place for cultivating the mind and body, was not exactly a healthy place, as it often functioned as a breeding ground for infection. The main school diseases in Copainalá were of an infectious-contagious origin, due to contaminated drinking water and poor public sanitation.